Awareness of the Food-Based Diet Guidelines, Eating Practices, and Preferred Sources of Nutrition Information of Employees in an Open University in the Philippines - Myra D Oruga; Jelaine Real Bagos (Faculty of Nursing Universitas Padjadjaran, 2021)
Background: Physical inactivity and unhealthy diet are considered as major risk factors in the development of the “fatal four” Non-communicable Diseases (NCDs) (WHO, 2018). As the University of the Philippines Open University (UPOU) adopts a sedentary work lifestyle with most of the employees spending long hours at the office sitting in front of a computer screen, the university must be able to promote health and wellness in the workplace, particularly healthy eating. Purpose: Thus, the study aimed to determine UPOU employees’ awareness of the Food-based Dietary Guidelines (FBDGs), adherence to the 2012 Nutritional Guidelines for Filipinos (NGF), and preferred sources of information on healthy eating to provide insights for the development of nutrition interventions in the university. Methods: A total of 85 healthy employees aged 19-59 years old accomplished an online adapted survey from February to April 2019 which included questions on awareness of the four FBDGs–2012 NGF; Kumainments (simplified version of NGF); Daily Nutritional Guide Pyramid (DNGP); and Pinggang Pinoy (a plate-like pictorial model), eating practices relative to the 2012 NGF, and preferred sources of information on the FBDGs. Data were analyzed using descriptive statistics. Results: Results of the study showed that most of the respondents were not aware of the FBDGs. Among those who were aware, only a few have read the FBDGs. Adherence to the guidelines was also low as reflected by a very low percentage of respondents practicing the messages on the recommended frequency of intake of food groups. Conclusion: Results suggest conducting lectures or seminars and producing video materials about nutrition which can be uploaded in UPOU’s online repository of multimedia resources and social media sites to promote healthy eating practices among UPOU employees and ensure a healthy and sustainable workforce.